DOSE OPTIMIZATION AND PHARMACOKINETIC/PHARMACODYNAMIC INTEGRATION OF AMOXICILLIN IN LOHI SHEEP ( Ov is aries) AND BEETAL GOATS - ( C apra hircus) M. A. Abid; Z. Manzoor; U. Naz; M. M. Ashraf (Journal of Animal and Plant Sciences, 2018)
The present study aimed to investigate the interspecies variations in relation to pharmacokinetic profile and optimal dosage regimen of amoxicillin in Lohi sheep and Beetal goats. For this purpose, 16 healthy, adult animals, 8 from each species of Lohi sheep were selected. The animals were 1-2 years of age and 35-45 kg body weight. Amoxicillin was injected as a single intramuscular dose of 15 mg/kg body weight to each animal. Blood samples were collected at ® specific time intervals over 24 hrs. Plasma drug concentrations and time data was calculated by WinNonlin for the estimation of pharmacokinetic parameters. Optimal dosage of amoxicillin was also calculated in both species. The elimination half-life and mean residence time were higher ( P < 0.05) in Beetal goats than Lohi sheep indicating the slow elimination of the drug in Beetal goats. A priming dose of amoxicillin of 21.6 ± 24.4 mg/kg body weight was suggested with a maintenance dose of 15.7 ± 18.9 mg/kg likely to be repeated every 24 hours in order to provide successful treatment against bacteria with susceptibility of minimum inhibitory concentration (MIC < 1.6 µg/mL) in Lohi sheep and Beetal goats respectively. where its two metabolites (amoxicilloic acid and
Keywords: Amoxicillin; Lohi sheep; Beetal goats; Pharmacokinetics; Dosage regimen.